2015
DOI: 10.1016/j.jmbbm.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Improving hydrogels׳ toughness by increasing the dissipative properties of their network

Abstract: a b s t r a c tThe weak mechanical performance and fragility of hydrogels limit their application as biomaterials for load bearing applications. The origin of this weakness has been explained by the low resistance to chains breakage composing the hydrogel and to the cracks propagation in the hydrogel submitted to loading conditions. These low resistance and crack propagation were in turn related to an insufficient energy dissipation mechanism in the hydrogel structure. The goal of this study is to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…, this composition resulted in the highest toughness. Thus, the absence of macrophase separation as well as a certain balance between stiffness and extensibility result in good mechanical properties, which is in agreement with literature[20] [29].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…, this composition resulted in the highest toughness. Thus, the absence of macrophase separation as well as a certain balance between stiffness and extensibility result in good mechanical properties, which is in agreement with literature[20] [29].…”
supporting
confidence: 91%
“…Toughness (WTensile) was used as a parameter for the resistance to fracture of a hydrogel under stress, and determined by integrating the stress-strain curve (area under the curve). A tough hydrogel is characterized by a balance between strength and elongation[20].2.6 Cell culture Circular specimens (n=6) of single polymer hydrogels and hybrid hydrogels with a diameter of 12 mm and a thickness of 1 mm were placed in a 48 well cell culture plate. A rubber ring with an outer diameter of 12 mm was put on top of the specimens to prevent floating.…”
mentioning
confidence: 99%
“…The combination of GelMA and HAMA into hybrid hydrogels brings together the advantages of both, and increased amounts of HAMA have already been reported to enhance the mechanical properties of GelMA gels [15]. However, the outstanding biological performance of hydrogels is often eclipsed by their compromised mechanical properties [23]. Mixtures of fibrous collagen hydrogels with non-fibrillar agarose have been proposed as a strategy to obtain collagen-based matrices of enhanced mechanical properties [11,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] In parallel, the high damping properties observed in the develop hydrogels provided load and crack resistance under the loading conditions of such tissues. 12,18 It has been already shown that HEMA-based hydrogels can partially degrade when they are cross-linked to some natural polysaccharides molecules such as chitosan, 22 dextran-based molecules, 7,40 hyaluronic acid and poly(lactic acid) PLA. 35 Due to the complexity of the functionalization of most of these molecules, their high molecular weight, and their mechanism of cross-linking, resulting hydrogels usually have very poor mechanical properties and cannot be used for load-bearing applications.…”
Section: Discussionmentioning
confidence: 99%